2008
DOI: 10.3201/eid1404.061366
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinvasion byMycoplasma pneumoniaein Acute Disseminated Encephalomyelitis

Abstract: We report the autopsy fi ndings for a 45-year-old man with polyradiculoneuropathy and fatal acute disseminated encephalomyelitis after having Mycoplasma pneumoniae pneumonia. M. pneumoniae antigens were demonstrated by immunohistochemical analysis of brain tissue, indicating neuroinvasion as an additional pathogenetic mechanism in central neurologic complications of M. pneumoniae infection.A 45-year-old, previously healthy man had fever, pain in the extremities, nasal discharge, and cough with nonpurulent sput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 13 publications
2
39
0
2
Order By: Relevance
“…Because of its diverse distribution of affected areas, an indirect mechanism has been postulated, namely, immune complexmediated vasculopathy [Behan et al, 1986;Guleria et al, 2005;Gupta et al, 2009]. On the other hand, recent studies on patients with acute disseminated encephalomyelitis have demonstrated the presence of M. pneumoniae genome in the cerebrospinal fluid [Matsumoto et al, 2009;Riedel et al, 2001;Yiş et al, 2008], or the presence of M. pneumoniae antigens inside the macrophages in the brain tissue [Stamm et al, 2008]. Thus it is highly possible that a direct mechanism, namely, vasculitis as a consequence of cytokine activation by M. pneumoniae, is responsible for some instances of acute disseminated encephalomyelitis.…”
Section: Acute Disseminated Encephalomyelitismentioning
confidence: 99%
“…Because of its diverse distribution of affected areas, an indirect mechanism has been postulated, namely, immune complexmediated vasculopathy [Behan et al, 1986;Guleria et al, 2005;Gupta et al, 2009]. On the other hand, recent studies on patients with acute disseminated encephalomyelitis have demonstrated the presence of M. pneumoniae genome in the cerebrospinal fluid [Matsumoto et al, 2009;Riedel et al, 2001;Yiş et al, 2008], or the presence of M. pneumoniae antigens inside the macrophages in the brain tissue [Stamm et al, 2008]. Thus it is highly possible that a direct mechanism, namely, vasculitis as a consequence of cytokine activation by M. pneumoniae, is responsible for some instances of acute disseminated encephalomyelitis.…”
Section: Acute Disseminated Encephalomyelitismentioning
confidence: 99%
“…Some of the perivascular macrophages revealed ''M. pneumoniae antigens inside macrophages present in the inflammatory infiltrate…'' [13]. The authors interpreted the latter finding as evidence of ''neuroinvasion'', which would confirm the hypothesis that direct infection may be the most probable pathomechanism for acute encephalitis in mycoplasmal infections.…”
Section: Discussionmentioning
confidence: 85%
“…The fourth was that of a 45-year-old male with the onset of neurological symptoms 7 days after the onset of fever, and death 10 days after the onset of neurologic symptoms. Postmortem examination revealed cerebral edema, ADEM, and hemorrhagic foci consisting of fibrinoid necrosis of small veins, perivascular necrosis and a mixed neutrophil-macrophage infiltrate [13]. These latter findings are most consistent with acute hemorrhagic leukoencephalitis of Hurst, considered by most to be a hyperacute form of ADEM [12].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Más excepcional es el ataque directo al tejido nervioso, especialmente en niños, en quienes produce meningoencefalitis bacterianas, aunque algunas sean defi nidas como meningitis asépticas 5 . Sin embargo, lo clásico, sigue siendo que tanto el compromiso neurológico, vascular o hematológico, tengan un patomecanismo inmunomimético a partir de los glicolípidos y lipoproteínas, de la cobertura plasmática y del citoplasma bacteriano, capaces de activar respuestas autoinmunes contra lipoestructuras homólogas 4 .…”
Section: Discussionunclassified